Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10681-015-1496-y
|View full text |Cite
|
Sign up to set email alerts
|

Response to S1 recurrent selection for resistance to two stem borers, Busseola fusca and Chilo partellus, in two tropical maize populations

Abstract: Stem borers, Busseola fusca and Chilo partellus, are among the key devastating lepidopteran insect pests of maize causing grain yield losses. Recurrent selection studies for stem borer resistance in maize are limited. However, maize populations carrying resistance genes to these stem borers have not been exploited fully in breeding programmes. The objective of the study was to separately improve resistance to B. fusca and C. partellus stem borers for two maize populations CML395/MBR C5 Bc and CML444/MBR/MDR C3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Asghar and Mehdi (2010) also showed that the estimates of broad-scense heritability, from S1 families, using an open pollinated sweet maize population, were (0.38) for grain yield, (0.77) for 100-kernel weight, (0.72) for cob length, (0.67) for plant height, and (0.57) for days to silking. Mwimali et al (2015) found that the broadscense heritability estimates from S 1 families for grain yield were 95.7, 93.5 and 98.4% for cycle 0, cycle 1 and cycle 2, separately, in the population CML395/MBRC5BC. These findings were higher than the present estimates however; estimates of heritability differ considerably from one study to another depending on the method of evaluation and number of replications.…”
Section: Estimation Of Heritabilitymentioning
confidence: 94%
“…Asghar and Mehdi (2010) also showed that the estimates of broad-scense heritability, from S1 families, using an open pollinated sweet maize population, were (0.38) for grain yield, (0.77) for 100-kernel weight, (0.72) for cob length, (0.67) for plant height, and (0.57) for days to silking. Mwimali et al (2015) found that the broadscense heritability estimates from S 1 families for grain yield were 95.7, 93.5 and 98.4% for cycle 0, cycle 1 and cycle 2, separately, in the population CML395/MBRC5BC. These findings were higher than the present estimates however; estimates of heritability differ considerably from one study to another depending on the method of evaluation and number of replications.…”
Section: Estimation Of Heritabilitymentioning
confidence: 94%
“…Suitable maize germplasm should have resistance to both B. fusca and C. partellus. Recent reports indicate that climate change has led to C. partellus increasingly displacing B. fusca from the high altitude areas in Kenya (Mailafiya et al, 2011;Tefera et al, 2011;Mwimali et al, 2015). Furthermore, farmers exchange maize germplasm across agroecologies, therefore, the need to investigate the reaction of these tropical maize inbred lines for resistance to these borers becomes paramount.…”
Section: Introductionmentioning
confidence: 99%